Avaliação dos exames de proteínas totais e desidrogenase lática para a classificação de transudatos e exudatos pleurais: redefinindo o critério clássico de light com nova abordagem estatística - Maranhão, Bernardo Henrique Ferraz (2010)
Objectives: To propose new reference values and their respective diagnostic parameters of the total proteins and lactic desidrogenase (LDH) dosage exclusively in the pleural fluid to diagnose pleural exudates and transudates. To compare the performance of the new criterion with the classical Light´s criteria. Methods: 181 patients selected from 2003 to 2006. Results submitted to ROC curve. Results: Using Light s criteria we reach a sensivity of 99.8% (97.8-101.8), specificity of 68.6% (58.3- 76.6) and accuracy of 94.5% (87.5- 97.2) to exudates (152 patients). Sensivity of 76.1% (66.7 83.3), specifity of 90.1% (82.5 94.4) and accuracy of 87.65 (80.1 93.02) for the diagnosis of pleural transudates (29 patients). Isolated analysis of total protein with level >3.4g/dL and LDH > 328.0 U/L in pleural fluid had a sensivity, specificity and accuracy of 99.4% (98.7 99.7), 72.6% (69.7 75.2), 99.2% (98.4 99.5) respectively. The accuracy of this new approach was significantly higher than Light s criteria to diagnose exudates (p=0.0022). Conclusions: The study of the classical Light´s criteria in brazilian cases were similar to the original study. The new classification criteria for distinguishing between pleural exudates and transudates, with measurements of total proteins and LDH in pleural fluid alone, reached statistical and clinical significance when validated against the classical Light´s criteria.